Distinct selective forces and Neanderthal introgression shaped genetic diversity at genes involved in neurodevelopmental disorders - Alessandra Mozzi (Nature Portfolio, 2017)
Abstract In addition to high intelligence, humans evolved specialized social-cognitive skills, which are specifically affected in children with autism spectrum disorder (ASD). Genes affected in ASD represent suitable candidates to study the evolution of human social cognition. We performed an evolutionary analysis on 68 genes associated to neurodevelopmental disorders; our data indicate that genetic diversity was shaped by distinct selective forces, including natural selection and introgression from archaic hominins. We discuss the possibility that segregation distortion during spermatogenesis accounts for a subset of ASD mutations. Finally, we detected modern-human-specific alleles in DYRK1A and TCF4. These variants are located within regions that display chromatin features typical of transcriptional enhancers in several brain areas, strongly suggesting a regulatory role. These SNPs thus represent candidates for association with neurodevelopmental disorders, and await experimental validation in future studies.